2009
DOI: 10.1016/j.ahj.2008.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Common endothelial progenitor cell assays identify discrete endothelial progenitor cell populations

Abstract: Background-Multiple measures of endothelial progenitor cells (EPCs) have been described, but there has been limited study of the comparability of these assays. We sought to determine the reproducibility of and correlation between alternative EPC assay methodologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 36 publications
3
29
0
1
Order By: Relevance
“…These markers are more reliable and accurate detectors of EPCs than other EPC culturebased assays (13). Interestingly, we also identified trends toward lower numbers of other exploratory markers of EPCs including cell surface expression of CD34…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…These markers are more reliable and accurate detectors of EPCs than other EPC culturebased assays (13). Interestingly, we also identified trends toward lower numbers of other exploratory markers of EPCs including cell surface expression of CD34…”
Section: Discussionmentioning
confidence: 61%
“…EPC number was assayed using flow cytometry on the basis of cell-surface expression of CD133, CD34, CD146, and CD14 as well as on the basis of aldehyde dehydrogenase (ALDH) activity, a property of stem cells, but lacking in more differentiated tissues, a method that is more precise than other EPC assays (12,13). Briefly, peripheral blood mononuclear cells (MNCs) were isolated using density gradient centrifugation and washed, and the relative level of EPCs in the MNC population was determined.…”
Section: Laboratory Proceduresmentioning
confidence: 99%
“…ALDHbr cells from human bone marrow are highly enriched in progenitors that give rise to multipotent mesenchymal cells [25,26]. Endothelial progenitor cells are also highly enriched in human ALDHbr populations from bone marrow [25,26] and normal peripheral blood [35,36]. In the context of tissue repair, human ALDHbr cells, especially cells derived from bone marrow, can provide a mixture of potential progenitor and, as discussed below, paracrine activities from a variety of stem cell types.…”
Section: Aldhbr Cells From Sources Of Hematopoietic Graft In Transplamentioning
confidence: 99%
“…Povsic et al [35,36] reported that the number of ALDHbr cells circulating in the blood of cardiovascular patients was inversely correlated with the extent of coronary artery disease. This group suggested that circulating ALDHbr cell levels could be used to assess risk of cardiac disease and to monitor the efficacy of therapeutic interventions.…”
Section: Aldhbr Cell From Human Cb and Bone Marrow In Repair Of Ischementioning
confidence: 99%
“…The EPC number was assayed using flow cytometry based on cell surface expression of CD34+CD133+ aldehyde dehydrogenase bright (ALDH br ) activity (16,17). Briefly, PBMCs were isolated using density gradient centrifugation and were washed, and relative level of EPCs in the mononuclear cell population was determined.…”
Section: Study Proceduresmentioning
confidence: 99%